PENDAPATAN PETANI PADA PENGGUNAAN LAHAN SAWAH IRIGASI DI KELURAHAN TEJOSARI KECAMATAN METRO TIMUR KOTA METRO - Yulia Ely Sesari; Sudarmi Sudarmi; Sugeng Widodo (JPG (Jurnal Penelitian Geografi), 2013)
The aim of this research was to find out information on farmers’ income on the use irrigation farming in Tejosari District, East Metro, Metro City in 2012. This study focused on (1) the land area for farming, (2) the amount of farmers’ working capital to do agriculture, (3) farmers’ income on the use of irrigation farming.The researcher used descriptive method for this research. The population was 222 family heads of irrigation farming farmers, while the samples were 30% which were 66 family heads. As the data collecting technique, the researcher used observation, documentation, and a structured interview.The results of research: (1) In a farmer rice cultivation, there were 25 (37,88%)  farmers who cultivated the average area of 0,64 ha, and there were 19 (39,58%) farmers in the average area of  0,61 ha who cultivated other plants excluding rice. (2) To cultivate rice, there were 65 (98,48%) farmers who used capital working for rice cultivation which was about Rp 1.363.504, and there were 46 (95,84%) farmers who used capital working for other cultivation which was about  Rp 650.361. (3) There were 46 (69,7%) farmers whose total income was about Rp 447.101 per month. Keywords: land area, capital working, and income